THE EFFECT OF AUDIT COMPLEXITY, FINANCIAL DISTRESS AND INSTITUTIONAL OWNERSHIP ON AUDIT REPORT LAG: (Empirical Study on Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period) - Arif Arya Bimo; Intan Rahma Sari (Transpublika Publisher, 2022)
This research was carried out on property and real estate sector companies during the time period 2017-2021, with the goal of determining and proving that Audit Complexity, Financial Distress, and Institutional Ownership will affect the Audit Report Lag. The sample companies for this study were chosen at random. In addition to dependent variables, this investigation also takes into account independent factors including Audit Complexity, Financial Distress, and Institutional Ownership. The method of research that was utilized in this investigation was descriptive research that took a quantitative approach. Purposive sampling was utilized as the method of sampling throughout this investigation. Secondary data and other data collecting methods, notably documentation, were used for the purpose of gathering information for this study. The research was carried out on 42 firms from the property and real estate sector that were listed on the Indonesia Stock Exchange between 2017 and 2021. Statistical analysis carried out with Eviews 9 The findings of the experiment demonstrate that Audit Complexity influences Audit Repot Lag, whereas Financial Distress policies and institutional ownership do not have any bearing on Audit Repot Lag. In addition, the results of this study demonstrate that Audit Complexity, Financial Distress, and Institutional Ownership all have an effect on Audit Report Lag simultaneously.